2007
DOI: 10.1007/s00280-007-0612-7
|View full text |Cite
|
Sign up to set email alerts
|

Erufosine, a novel alkylphosphocholine, in acute myeloid leukemia: single activity and combination with other antileukemic drugs

Abstract: Purpose Alkylphosphocholines represent a new class of cytostatic drugs with a novel mode of action. Erufosine (ErPC3), the first compound of this class that can be administered intravenously, has recently been shown to be active against human tumor and leukemic cell lines. Methods In order to evaluate the antileukemic potential of ErPC3 in acute myeloid leukemia (AML) the lethal concentration 50% (LC 50) was determined using WST-1 assay. For analysis of cell death, staining for Annexin V and activated caspase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 22 publications
2
26
0
4
Order By: Relevance
“…Erufosine, either alone or in combination with other chemotherapeutic agents and ionic radiation, induces apoptosis in different kinds of cancer [141] (Table 3). Erufosine combined with etoposide and cytarabine acts additively in acute myeloid leukemia [142] . Erufosine causes cell death in acute myeloid leukemia by JNK 1/2 activation and ERK 1/2 dephosphorylation, leading to apoptosis [143] .…”
Section: Akt Inhibitorsmentioning
confidence: 99%
“…Erufosine, either alone or in combination with other chemotherapeutic agents and ionic radiation, induces apoptosis in different kinds of cancer [141] (Table 3). Erufosine combined with etoposide and cytarabine acts additively in acute myeloid leukemia [142] . Erufosine causes cell death in acute myeloid leukemia by JNK 1/2 activation and ERK 1/2 dephosphorylation, leading to apoptosis [143] .…”
Section: Akt Inhibitorsmentioning
confidence: 99%
“…64 In this connection, it is important to emphasize that ErPC3 synergizes in vitro with chemotherapeutic drugs commonly used for treating AML ErPC3-mediated cyotoxicity in AML AM Martelli et al patients. 18 ErPC3 has been studied in a phase I dose escalation trial at the University of Munich. Thereby, plasma steady state levels of 10-20 mM ErPC3 after repeated intravenous application have been reached without showing toxicity (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Recently, the in vitro cytotoxic effect of ErPC3 in AML cells has been documented. 18 In this study, we have further investigated the mechanisms that could underlay ErPC3 cytotoxicity in AML cells. We demonstrated that ErPC3 activated JNK 1/2.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, o tratamento antitumoral por via oral com miltefosina é dificuldado pela toxicidade gastrointestinal assim como a administração intravenosa leva a ação hemolítica, o que limita seu uso (LINDNER et al, 2008;FIEGL et al, 2008;SEIFERT et al, 2007;AGRESTA et al, 2003 A grande variação de incidência geográfica nas taxas de câncer de colo do útero reflete diferenças na disponibilidade de triagem, que permite a deteccção e remoção de lessões pré-cancerosas, e prevalência da infecção pelo virus do papiloma (HPV) (VACCARELLA et al, 2013;BRUNI et al, 2010;FORMAN et al, 2012 …”
Section: Lista De Abreviações E Siglasunclassified